Introduction of suitable species for planting in gaps of different size (case study: Loveh forest, Golestan, Iran) - Pejman PARHIZKAR; Khosro SAGHEB-TALEBI; Yaser SHAHINI; Maryam TEIMOURI (Journal of Forest Science, 2017)
This study was carried out in Loveh forest, north of Iran. We measured the quantitative characteristics of seedlings including collar diameter (measured at 1 cm above the soil surface), height, and current annual height increment and calculated the mean annual increments of height and diameter. Ten gaps with the same climatic, edaphic and topographic conditions were selected. In each gap, two transects, 2 m wide, were laid along the longest (North-South) and the shortest (West-East) axis. Nine sampling microplots, 4 m2 area, were established: one at the centre, four at the edges and four under the canopy within the transects. Results showed that the highest frequency of seedlings was seen in medium-size gaps (200-500 m2). Quantitative characteristics of oak seedlings were better in small and medium-size gaps. There was a significant difference in the length of spring shoots, mean annual increment of height and mean annual increment of diameter between the species. Hornbeam, wild service and wild cherry seedlings are recommended for faster gap recovery, as the results showed that these species had the highest values of studied variables.